A bibliography of Greek New Testament manuscripts - Elliott, J. K. (Novum Testamentum, Supplements, 2015)
This bibliography is a comprehensive listing of books, facsimiles, collations and articles relating to some 3,500 Greek New Testament manuscripts, including references to photographic plates and albums. These are divided into the conventional categories of papyri, majuscules, minuscules and lectionaries, as classified in the current Gregory-Aland register. This third revised edition supersedes the two previous editions. Entries from those earlier editions and from three supplements, published as articles in Novum Testamentum , as well as newly published material, are to be found here. The author is grateful for the help of editor Barbara Cangemi.